2014
DOI: 10.1080/21663831.2014.932858
|View full text |Cite
|
Sign up to set email alerts
|

New Solid Solution MAX Phases: (Ti0.5, V0.5)3AlC2, (Nb0.5, V0.5)2AlC, (Nb0.5, V0.5)4AlC3and (Nb0.8, Zr0.2)2AlC

Abstract: AlC. Rietveld analysis of powder X-ray diffraction patterns was used to calculate the lattice parameters and phase fractions. Heating Ti, V, Al and C elemental powders-in the molar ratio of 1.5:1.5:1.3:2-to 1, 450 • C for 2 h in flowing argon, resulted in a predominantly phase pure sample of (Ti 0.5 , V 0.5 ) 3 AlC 2 . The other compositions were not as phase pure and further work on optimizing the processing parameters needs to be carried out if phase purity is desired.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(42 citation statements)
references
References 44 publications
(39 reference statements)
2
40
0
Order By: Relevance
“…Hu et al have reported a partial list of about 70 new MAX phases in the period 2004-2013 [7]. Recently, Naguib et al [8] reported a large number of work (68 quaternary MAX phases) on the solid solutions where existing phases are mixed. These approaches yield the new phases [9,10] and/or other ordered quaternary phases [8, 11 -14].…”
Section: Introductionmentioning
confidence: 99%
“…Hu et al have reported a partial list of about 70 new MAX phases in the period 2004-2013 [7]. Recently, Naguib et al [8] reported a large number of work (68 quaternary MAX phases) on the solid solutions where existing phases are mixed. These approaches yield the new phases [9,10] and/or other ordered quaternary phases [8, 11 -14].…”
Section: Introductionmentioning
confidence: 99%
“…Although the stoichiometry is slightly off from VTi2AlC2, this prediction can be compared to the experimentally obtained (V0.5Ti0.5)3AlC2 solid solution. 21 For TiM2AlC2 in Fig. 3 …”
Section: Mti2alc2 and Tim2alc2mentioning
confidence: 99%
“…In particular, solid solutions on the M-site include, e.g., (Ti,M)2AlC where M = V, Nb, Ta, Cr, [8][9][10][11] (V,M)2AlC where M = Nb, Ta, Cr, 9,12 (Cr,Mn)2AC where A = Al, Ga, Ge, 3,[13][14][15][16][17][18][19] (Ti,V)3AC2 where A = Al, Ge, 20,21 and (V,M)4AlC3 where M = Ti, Nb. 20,21 Adding a fourth element has also been demonstrated by realization of TiCr2AlC2, 22,23 V1.5Cr1.5AlC2, 12 TiMo2AlC2, 24,25 and Ti2Mo2AlC3, 24 which all are recent discoveries of chemically ordered quaternary MAX phases, with atomic layers composed of a single element only. This raises the question why certain combinations of M elements form layered chemically ordered MAX phases, while other combinations result in a solid solution.…”
Section: Introductionmentioning
confidence: 99%
“…19 When solid solutions are taken into account, the situation is not very different. For instance, Al-containing Ti/V and Ti/Nb solid solutions exist, 20 but these do not add any new elements to those already known to bond to Al. There are few exceptions, however, wherein a solid solution contains a M element, that do not generally bond to Al, such as Zr in (Nb 0.8 ,Zr 0.2 ) 2 AlC, 20 and (Nb 0.6 ,Zr 0.4 ) 2 AlC, 21 or Mn in (Cr x ,Mn 1Àx ) 2 AlC.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Al-containing Ti/V and Ti/Nb solid solutions exist, 20 but these do not add any new elements to those already known to bond to Al. There are few exceptions, however, wherein a solid solution contains a M element, that do not generally bond to Al, such as Zr in (Nb 0.8 ,Zr 0.2 ) 2 AlC, 20 and (Nb 0.6 ,Zr 0.4 ) 2 AlC, 21 or Mn in (Cr x ,Mn 1Àx ) 2 AlC. 22,23 In all these examples, however, the mole fraction of the non-Al bonding M element is less that 0.5 of the total M-content.…”
Section: Introductionmentioning
confidence: 99%